(untitled) (American Journal of Islam and Society, 1991)
Little data are available about the nature of stress which Muslims in North America frequently endure. Muslim scholars have not attempted to define the major stressors these Muslims experience, nor have they furnished Muslims with an inocuIation program that integrates Islamic beliefs with cognitive techniques in order to change stress quality and quantity. The development of such a program, however, is not possible without theoretical foundations that employ the findings of stress research. On the other hand such a theory, if fuIly deveIoped, is not functional without empirical data to sustain its basic propositions. Hence, the purpose of this paper is to: a) develop the theoretical foundations of the interreIationship between stress cognition and Islamic beliefs; b) present a stress cognition paradigm that explains the moderation function of certain Islamic beliefs; and c) incorporate certain Islamic beliefs in the application of the cognitive techniques of stress management. The Relationship between Stress Cognition and Religious Beliefs Stress is defined as the outcome of the cognitive process through which a person interprets and attaches meaning(s) to an event. Selye (1974) explains it as being the negative or positive cognitive appraisal that causes the individual to perceive an event as stressful. Based on the outcomes of the cognitive appraisal, Selye distinguishes between two types of stress: a) distress or pathogenic stress “which goes beyond people’s optimum arousal point so that performance and health deteriorate” (Savery 1986, 17), and b) eustress, which ...